Language classification : history and method - Campbell, Lyle; Poser, William John (Cambridge University Press, 2008)
How are relationships established between the world's languages? This is one of the most topical and most controversial questions in contemporary linguistics. The central aims of the book are to answer this question, to cut through the controversies, and to contribute to research in distant genetic relationships. In doing this the authors aim to: (1) show how the methods have been employed; (2) reveal which methods, techniques, and strategies have proven successful and which ones have proven ineffective; (3) determine how particular language families were established; (4) evaluate several of the most prominent and more controversial proposals of distant genetic relationship (such as Amerind, Nostratic, Eurasiatic, Proto-World, and others); and (5) make recommendations for practice in future research. This book will contribute significantly to understanding language classification in general.
Keywords: Comparative linguistics; Language and languages : Classification; kieli ja kielet; kielihistoria; kielikunnat; kielisukulaisuus; kielitypologia; vertaileva kielitiede; språk; språkhistoria; språkstammar; språkfrändskap; språktypologi; jämförande språkvetenskap